(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. Esperienze normative - 3. Nello spazio giuridico europeo e internazionale - 4. Valida e inefficace - 5. Una ragionevole normativa penale - 6. Rigidità e flessibilità - 7. Fondati timori - 8. Us and Them - 9. Le culture tra eguaglianza e differenze – 10. Conclusioni. Cultural Defenses between Monoculturalism and Multiculturalism ABSTRACT: In an increasingly globalized world, individuals and groups are seeking to have their own culture respected, maintaining their cultural diversity in the face of growing globalization. These claims are connected with the formal conceptions of the principle of equality, which often produces substantial and discriminatory inequalities. This situation becomes even more complicated when related to the specific field of criminal law concerning cultural defenses. The author analyses the different approaches to cultural defenses, those oscillating from multiculturalism to monoculturalism, taking into account the Italian and European-international legal context.